Surface functionalization of carbon fabric towards high-performance epoxy composites via enhanced fiber–matrix interfacial strength and intergrowth charring behavior - L. Zhang; Y. Ou; D.-Y. Wang (eXPRESS Polymer Letters, 2021)
The development of carbon fabric reinforced epoxy (CF/EP) composites with excellent mechanical properties and high flame retardancy is desired in both scientific and industrial communities. In this work, the phosphorus-containing flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide (DOPO) based amine functional silane coupling agent was coated on carbon fabric, aiming to promote the interfacial charring behavior, and at the same time, improve the fiber-matrix interfacial strength. With only a small proportion of the hybrid Si/N/P coating on the fiber surface, the resultant composite laminate showed a 26 and 31% reduction in peak heat release rate and smoke production rate, respectively. Under the combustion, the surface grafted phosphorus compounds effectively promoted the interfacial charring behavior of EP composites. An integrated and dense char layer composed of carbon fabric with sealed gaps was formed to protect the underlying polymer materials in the condensed phase. In addition, the fiber push-in test clearly revealed an increased fibermatrix interfacial strength (35%) due to the existence of amine groups on the fiber surface. The provided Si/N/P hybrid surface functionalization strategy proved to be an effective approach to prepare high-performance flame retardant CF/EP composite.